SPACE WEATHER AND THE STATE OF CARDIOVASCULAR SYSTEM OF A HEALTHY HUMAN BEING - Samsonov, S. N.; Manykina, V. I.; Krymsky, G. F.; Petrova, P. G.; Palshina, A. M.; Vishnevsky, V. V. (Одеські астрономічні публікації, 2013)
The term “space weather" characterizes a state of the near-Earth environmental space. An organism of human being represents an open system so the change of conditions in the environment including the near-Earth environmental space influences the health state of a human being. In recent years many works devoted to the effect of space weather on the life on the Earth, and the degree of such effect has been represented from a zero-order up to apocalypse. To reveal a real effect of space weather on the health of human being the international Russian- Ukrainian experiment "Geliomed" is carried out since 2005 (http://geliomed.immsp.kiev.ua) [Vishnevsky et al., 2009]. The analysis of observational set of data has allowed to show a synchronism and globality of such effect (simultaneous manifestation of space weather parameters in a state of cardiovascular system of volunteer groups removed from each other at a distance over6000 km). The response of volunteer’ cardiovascular system to the changes of space weather parameters were observed even at insignificant values of the Earth’s geomagnetic field. But even at very considerable disturbances of space weather parameters a human being healthy did not feel painful symptoms though measurements of objective physiological indices showed their changes.